Treatment of a Large Hemorrhagic Midbrain Cavernoma Within the Silvian Aqueduct in a Five-Year-Old Girl—A Case Report - Matthias Krause; Armin-Johannes Michel; Johannes Koch; Johann Gradl; Johannes A. R. Pfaff; Christoph J. Griessenauer; Lorenz Stana-Hackenberg (Children)
Brain stem cavernomas are exceedingly rare in pediatric populations, with limited literature addressing their natural history, treatment guidelines, and counseling. We report the case of a 5-year-old girl presenting with acute neurological symptoms, including diplopia, gait ataxia, headache, and altered consciousness. Initial imaging revealed obstructive hydrocephalus caused by a hemorrhagic lesion near the pineal region. After emergency external ventricular drainage (EVD), most symptoms resolved except for diplopia. A subsequent MRI suggested a space-occupying hemorrhagic cyst in the tectal lamina, leading to endoscopic third ventriculostomy (ETV). During ETV, a large hemorrhagic mass at the aqueduct entrance was identified but not removed due to its fragility. Following ETV, the patient improved rapidly and was discharged. However, she was readmitted with recurrent symptoms and altered consciousness. An emergency MRI indicated a progressive hemorrhagic mass lesion compressing the midbrain, necessitating surgical intervention. The patient underwent suboccipital craniotomy using a telovelar approach. The intraoperative findings included cavernoma-like tissue within the aqueduct, which was successfully resected. Histopathology confirmed hemorrhagic and angiomatous tissue, excluding a primary brain tumor. Postoperatively, the patient showed significant, progressive neurological improvement, with mild internuclear strabism, trunk ataxia, and fatigue at the last follow-up. Six months later, a follow-up MRI and cerebral angiography showed no cavernoma remnants but identified a midbrain deep venous anomaly. This case underscores the feasibility of the microsurgical resection of midbrain cavernomas in symptomatic pediatric patients, highlighting the importance of the thorough assessment of atypical hemorrhagic midbrain lesions to exclude rare vascular malformations from differential diagnoses.